The Ability of Biofilms Formation and the Differences of Antifungal Susceptibility Pattern between Planktonic and Biofilm Candida sp. - Inayati Inayati; Praseno Praseno; Mustofa Mustofa (CV. Inara, 2026)
Candida sp. as human body's flora causes infections and its ability to create biofilms antifungals and host immune responses cannot reach it caused resistance to broad-spectrum antifungal. In this study, the antifungal susceptibility patterns of ketoconazole, itraconazole, and fluconazole against biofilms of Candida sp. will be determined, as well as the differences in susceptibility patterns between biofilm and planktonic Candida sp. The antifungal susceptibility of clinical isolates of both planktonic and biofilm Candida sp. determine by liquid dilution methode and the intensity of biofilm formation determined by Crystal Violet methode. Of the twenty-four Candida sp., 70.8% exhibited strong biofilm intensity, while 29.2% had moderate intensity. Planktonic Candida sp. exhibited a 100%, 78.9%, and 57.9% susceptibility pattern to fluconazole, ketokonazole, and itraconazole, respectively. Meanwhile, the sensitivity percentage decreased for biofilm Candida sp., which had sensitivity values of 31.6%, 21.1%, and 31.6%, respectively. Planktonic Candida sp. had MIC values ranging from 2 to about 33 times lower than those of biofilm Candida sp. Compared to planktonic Candida sp., the susceptibility pattern of biofilms revealed a lower sensitivity percentage. Planktonic Candida sp. had an average value ratio of 1.5 to 3.1 times, whereas Biofilm Candida sp. had MIC values 2 to > 33 times higher.